2016
DOI: 10.1155/2016/4723416
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial Electrolyte Transport Physiology and the Gasotransmitter Hydrogen Sulfide

Abstract: Hydrogen sulfide (H2S) is a well-known environmental chemical threat with an unpleasant smell of rotten eggs. Aside from the established toxic effects of high-dose H2S, research over the past decade revealed that cells endogenously produce small amounts of H2S with physiological functions. H2S has therefore been classified as a “gasotransmitter.” A major challenge for cells and tissues is the maintenance of low physiological concentrations of H2S in order to prevent potential toxicity. Epithelia of the respira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 106 publications
0
23
0
Order By: Relevance
“…The basolaterally localized Na ϩ /K ϩ -ATPase generates the electrochemical driving force for apical sodium entry via ENaC and, hence, vectorial, transepithelial sodium absorption. The precise mechanism of how H 2 S decreases Na ϩ /K ϩ -ATPase activity remains unknown (46). Studies using primary cultured alveolar epithelial and A549 cells demonstrated that hypoxia also impairs transepithelial sodium absorption due to inhibition of the Na ϩ /K ϩ -ATPase (13,34).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The basolaterally localized Na ϩ /K ϩ -ATPase generates the electrochemical driving force for apical sodium entry via ENaC and, hence, vectorial, transepithelial sodium absorption. The precise mechanism of how H 2 S decreases Na ϩ /K ϩ -ATPase activity remains unknown (46). Studies using primary cultured alveolar epithelial and A549 cells demonstrated that hypoxia also impairs transepithelial sodium absorption due to inhibition of the Na ϩ /K ϩ -ATPase (13,34).…”
Section: Discussionmentioning
confidence: 99%
“…Exogenous H 2 S exerts prosecretory and antiabsorptive actions in epithelia, leading to net transepithelial liquid secretion (46). On the basis of the general toxicity of excess H 2 S (48) Fig.…”
Section: Perspectives and Significancementioning
confidence: 99%
See 2 more Smart Citations
“…In rat, guinea pig and human colon preparations, H 2 S stimulates the secretion of chloride 15 . This is either due to direct actions on ion channels and transporters within the epithelial cells 18,19 , or indirectly by stimulating enteric secretomotor neurons 20 .…”
Section: Introductionmentioning
confidence: 99%